Dramatic Hypocrisies: Victorian Anxieties, Performative Selfhood, and Proto-Modernist Fluidity in Browning’s Monologues (IUBAT Review, 2026)
“Behind every polished monologue lies a fractured self, whispering through the cracks of Victorian decorum.” This study examines the evolving architecture of selfhood in Robert Browning’s dramatic monologues, revealing how Victorian anxieties about morality, gender, and institutional authority influence the performance of identity and prefigure modernist fluidity. The research examines Browning’s poetic project as a subversive critique of fixed selfhood, entrenched class structures, and the moral posturing of his age. Employing close textual analysis alongside historicist contextualization, the study interrogates Browning’s use of unreliable narrators—figures who, under the guise of confession, reveal the chasm between public virtue and private vice. These poetic personae serve not merely as characters but as vessels through which Browning exposes the ideological fault lines of his society. Findings reveal that Browning envisions identity not as an essence but as an emergence—a protean negotiation between self and sociality, mediated by performance, power, and colonial modernity. His work dismantles binaries of sincerity and artifice, virtue and vice, stability and fluidity. The novelty of the study lies in bridging his poetics to postmodern identity, reclaiming him as a proto-modernist voice. Ultimately, the research affirms Browning as a poet of transgression—one who weaponizes dominant paradigms to interrogate the very ground on which they stand.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 105-129